Riesgo Toxicológico por plomo en granos de soja (Glycine max L.) comercializados en el cantón Quevedo, Ecuador - Barragan Monrroy, Roberto (2024)
Lead, a highly toxic metal, can accumulate in the body through food intake, especially cereals and grains. Soybean, being a cereal, is characterized by its notable capacity for resistance to toxic metals, which makes it less susceptible to chemical and biological decomposition processes. The objective of this research is to quantify the concentrations of lead in soybeans and the toxicological risk to which the inhabitants of the Quevedo canton are exposed. To achieve this, random grain samples were collected monthly in triplicate (n=3) from four markets, along with a control sample. Subsequently, they were analyzed independently. The samples were weighed, calcined at 600°C for two hours, cooled and digested with concentrated nitric and hydrochloric acid. The digestates were diluted to 10 ml with 3% nitric acid and analyzed by atomic absorption spectrometry. The toxicological risk evaluation was carried out using the ATSDR Evaluation Guide for Environmental Environments, considering parameters such as EMEG, DE, IP, ME and RI. The average concentrations of lead in soybeans were 1.15 ± 0.13 mg. Kg-1, exceeding the limits allowed by INEN: 2013, Codex Alimentarius and the European Union (0.1 - 0 .2 mg/kg). However, toxicological evaluation suggests that local conditions are safe. Although no imminent risk to the population was found, the high concentrations of lead in soybeans are worrying, especially for children's health.